Vitamin C and glutathione supplementation: a review of their additive effects on exercise performance - Lee, E.; Park, H. Y.; Kim, S. W.; Kim, J.; Lim, K. (Physical Activity and Nutrition, 2023)
[Purpose] This review aimed to investigate the effects of vitamin C and glutathione supplementation on exercise performance. [Methods] We conducted a literature search across the PubMed, Google Scholar, and Web of Science databases using the keywords vitamin C, glutathione, antioxidants, exercise, and oxidative stress. [Results] The effects of vitamin C supplementation on exercise performance and oxidative stress levels are inconsistent. Glutathione, with its diverse forms of supplementation and methods, presents mixed outcomes. Vitamin C and glutathione have deeply interconnected antioxidant functions and are mutually essential to each other. Research investigating the combined intake of these two substances, which are intricately linked biochemically, and their effects on exercise performance remain largely unexplored. [Conclusion] Studies on the effects of vitamin C and glutathione intake on exercise have been conducted using diverse approaches; however, the results have not been consistent. Although an additive effect is anticipated with the combined intake of vitamin C and glutathione, research on this topic is currently insufficient, and further studies are required.